Consumer-Citizens of China The Role of Foreign Brands in the Imagined Future China - Tian, Kelly (Routledge Contemporary China Series, 2010)
This book presents a comprehensive examination of Chinese consumer behaviour and challenges the previously dichotomous interpretation of the consumption of Western and non-Western brands in China. The dominant position is that Chinese consumers are driven by a desire to imitate the lifestyles of Westerners and thereby advance their social standing locally. The alternative is that consumers reject Western brands as a symbolic gesture of loyalty to their nation-state. Drawing from survey responses and in depth interviews with Chinese consumers in both rural and urban areas, Kelly Tian and Lily Dong find that consumers situate Western brands within select historical moments. This embellishment attaches historical meanings to Western brands in ways that render them useful in asserting preferred visions of the future China. By highlighting how Western brands are used in contests for national identity, Consumer-Citizens of China challenges the notion of the "patriot's paradox" and answers scholars' questions as to whether Chinese nationalists today allow for a Sino-Western space where the Chinese can love China without hating the West. Consumer-Citizens of China will be of interest to students and scholars of business studies, Chinese and Asian Studies and Political Science. Kelly Tian is Professor of Marketing and holds the Anderson Chair of Business at New Mexico State University. Lily Dong is Associate Professor of Marketing at the University of Alaska at Fairbanks. Chapter One IMAGINING CHINA, IMAGINING BRANDS: Foreign Brands as Global Brands from the Imagined West; Western and Domestic Brands As Materials for Realizing an Imagined Future China; Obscured State Influence and Consumer Autonomy; Organization of the Book Chapter Two RETHINKING POPULAR NOTIONS OF CHINESE CONSUMERS' MOTIVES FOR RESPONDING TO WESTERN BRANDS: The Emulative Motive For Western Brand Consumption; The Patriotic Motive for Rejecting Western Brands; Rethinking the Primacy of the Emulative Motive for Consuming Western Brands; Rethinking "Consumer Nationalism" as Synonymous with Western Brand Boycotting; Chinese Consumers as Active Meaning Makers Chapter Three HIGHLIGHTED MOMENTS IN THE HISTORY OF BRANDED GOODS IN CHINA: The Emergence of Branded Goods in Late Imperial China; Branded Goods in Semi-colonial China of the Early 20 th Century; Branded Goods Since Gaige Kaifang- China's Economic Reform; Relevance of These Past Moments to Present-Day Brand Meanings Chapter Four FOREIGN BRANDS IN CHINA AS GLOBAL BRANDS FROM THE IMAGINED WEST: Overview of Research Method; Data Collection Sites; Our Data Collection Methods; Foreign Brands as Western Brands With Distinguishing Characteristics Chapter Five CHINESE NATIONAL NARRATIVES AND THE MEANINGS OF WESTERN BRANDS: The West as Experiential Venue, Western Brands as Instruments of Freedom; The West as Imperialist Oppressor, Western Brands as Instruments of Domination; The West as Subjugated, Conquered Western Brands as Redemption; The West as Economic Partner, Western Brands as Instruments of Economic Progress Chapter Six NATIONAL NARRATIVES IN IMAGINATIVE PROCESSING OF WESTERN BRAND PROMOTIONS: Imagined Consumption; Western Brand Producers' Efforts to Evoke Consumption Fantasies; Individual Psychological Processes of Enlivening Consumption Fantasies; Narratives and Imagined Identity Transformations From Western Brand Consumption; The Influence of East-West Narratives On the Processing of Western Brands Promotions; Discussion Chapter Seven CITIZEN-CONSUMERS IN AN AGE OF GLOBALIZATION